Não te conheço bem, mas já gostei de você! o efeito da marca na negligência da omissão nos diferentes níveis de necessidade cognitiva - Lopes, Evandro Luiz (2010)
Motivated by the growing number of brands created in recent years, and also by the asymmetry in disclosure of relevant information to the consumer in order to take assertive purchasing decisions, the main objective of this thesis is to identify the role of brand in omission neglect at different levels of cognitive needs. Since or once omission neglect is characterized by lack of consumer sensitivity to missing or unknown information, we have manipulated the extension of the attributes of a target object and its brand in six experiments carried out simultaneously. The data obtained from the sample of 1078 students from seven institutions of higher learning were compiled and analyzed using the analysis of variance. Among other findings, the statistical analysis allows us to conclude that: a) the brand of a product can reduce the omission neglect in the assessment process, especially when the evaluator has high cognitive needs, b) individuals with a low-context cognitive, on average, are insensitive to omission of information and conduct radical and extremely positive assessments, no matter the polarity of the available cognitive load, c) evaluating the extent of related and unrelated brand is heavily moderated by cognitive context level. This thesis also presents, in its last chapter, the limitations in the experiments and points out new pathways for further research on the theme.